16th AIAA/DLR/DGLR International Space Planes and Hypersonic Systems and Technologies Conference 2009
DOI: 10.2514/6.2009-7432
|View full text |Cite
|
Sign up to set email alerts
|

Proof-of-Principle Experiment of a Shock-Induced Combustion Ramjet

Abstract: By injecting and mixing the fuel upstream of the combustor and initiating the combustion of the fuel-air mixture by a shock wave in the combustor, shock-induced combustion ramjets offer the potential to drastically reduce the length and mass of scramjet propulsion systems. Based on extensive numerical gas dynamic and thermo-mechanical analysis, an axi-symmetric dual cone test object was designed and manufactured to demonstrate that it is possible to inject hydrogen into a high enthalpy supersonic air flow with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Therefore, scholars are interested in fuel injection near the leading edge of the ODE inlet and its premixing with the incoming airflow under the premise of avoiding premature ignition, and some efforts have been made [3,[7][8][9][10][11]. In the simulations conducted by Sislian et al [7][8][9] for cantilevered ramp injection, well-premixed flow conditions were achieved, while premature ignition was prevented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, scholars are interested in fuel injection near the leading edge of the ODE inlet and its premixing with the incoming airflow under the premise of avoiding premature ignition, and some efforts have been made [3,[7][8][9][10][11]. In the simulations conducted by Sislian et al [7][8][9] for cantilevered ramp injection, well-premixed flow conditions were achieved, while premature ignition was prevented.…”
Section: Introductionmentioning
confidence: 99%
“…In the simulations conducted by Sislian et al [7][8][9] for cantilevered ramp injection, well-premixed flow conditions were achieved, while premature ignition was prevented. Veraar and Mayer [10] performed a proof-of-principle experiment, injecting hydrogen into a high enthalpy supersonic airflow by a double-wedge injector configuration. During their test, the mixture was burnt by a strong oblique shock wave, and premature ignition was avoided successfully.…”
Section: Introductionmentioning
confidence: 99%
“…Marble et al[333] suggested 2856 using shock-induced mixing associated with the RMI to 2857 accelerate the mixing process between a cylindrical column of Hydrogen fuel and the ambient air. In a typical scramjet configuration (or a Shcramjet: shock-induced combustion ramjet[533]), the fuel jet is supersonic and is intersected by an oblique stationary shock at every cross-section along its length. The authors of[333] applied thin body theory to show that the spatial development of the cross-section of the cylindrical jet is equivalent to the temporal development of a fuel jet that is processed by a moving shock wave.…”
mentioning
confidence: 99%